Physical Extraction of Microorganisms From Water‐Saturated, Packed Sediment. (1st May 2014) - Ugolini, Fabio; Schroth, Martin H.; Bürgmann, Helmut; Zeyer, Josef
ABSTRACT: Microbial characterization of aquifers should include samples of both suspended and attached microorganisms (biofilms). We investigated the effect of shear, sonication, and heat on the extraction of microorganisms from water‐saturated, packed sediment columns containing established biofilms. Shear was studied by increasing flow velocity of the column eluent, sonication by treating the columns with ultrasound at different power levels, and heat by warming up the column eluent to different temperatures. Effluent cell concentrations were used as a measure of extraction efficiency. Dissolved organic carbon and adenosine tri‐phosphate (ATP) concentrations were used to corroborate cell‐extraction results. Additionally, ATP was used as an indicator of cell‐membrane integrity. Extraction quality was determined by comparing terminal‐restriction fragment length polymorphism (T‐RFLP) profiles of extracted bacterial communities with destructively sampled sediment‐community profiles. Sonication and heat increased the extraction efficiency up to 200‐fold and yielded communities comparable to the sediment community. These treatments showed high potential for in‐situ application in aquifers.